A Roadmap for Measurement-based Care Implementation in Intensive Outpatient Treatment Settings for Children and Adolescents. Issue 4 (2nd October 2022) - Childs, Amber W.; Connors, Elizabeth H.
ABSTRACT: Measurement-based care (MBC), the routine collection and use of patient-reported data to monitor progress and tailor treatment, has been predominantly studied in adult treatment settings. Although growing evidence supports MBC effectiveness with youth in outpatient settings and university training clinics, there is a substantial dearth of findings about successful implementation of MBC in "real world" youth treatment settings, particularly intensive settings offering group-based treatment. The current manuscript provides a foundational model of MBC implementation for "real world" intensive outpatient programs (IOP) for youth using the organizational framework of the Consolidated Framework for Implementation Research (CFIR). We also illustrate MBC implementation within a hospital-based adolescent psychiatric IOP, including enhancements to the foundational model and timely discussion of adjustments necessitated by the COVID-19 pandemic and transition to telehealth. Given the promising transdiagnostic and transtheoretical applicability of MBC, coupled with the MBC mandate for Joint Commission accredited health-care systems, IOP programs are well-positioned to adopt, implement and sustain MBC with careful attention to a phased, multilevel implementation approach.